The Effect of Auditor Competency and Organizational Support on Auditor Performance at the Selayar Islands District Inspectorate with Work-Life Balance as a Moderation - Nabila Fildzah Syakirah; Suhartono; Muhammad Sapril Sardi Juardi (Academic Bright Collaboration, 2025)
This study aims to examine the influence of auditor competence and organizational support on auditor performance with work-life balance as a moderating variable. This research is a quantitative study with a causality approach. The population in this study were auditors working at the Selayar Islands Regency Inspectorate, with the sampling technique using the census method or saturated sampling. The number of samples used in this study was 45 auditors consisting of first-time auditors, junior auditors, and middle auditors. The data used in this study were primary data obtained through direct questionnaire distribution to respondents. The results showed that auditor competence had a positive and significant effect on auditor performance. Conversely, organizational support did not have a significant effect on auditor performance. In addition, the results of the moderation regression analysis showed that work-life balance was not able to moderate the effect of auditor competence on auditor performance, but was able to moderate the effect of organizational support on auditor performance. The implications of this study indicate that auditor competence plays a dominant role in improving auditor performance, while work-life balance only functions as a moderating variable in the relationship between organizational support and auditor performance. The results also emphasize the importance of developing auditor competence and implementing organizational policies that support work-life balance to encourage sustainable auditor performance.